Corrigendum to “RIP1-RIP3-DRP1 pathway regulates NLRP3 inflammasome activation following subarachnoid hemorrhage”. Experimental Neurology. 2017 Sep: 295:116–124. (Experimental Neurology (2017) 295 (116–124), (S0014488617301425), (10.1016/j.expneurol.2017.06.003)) - Zhou, Keren; Shi, Ligen; ZhenWang,; Zhou, Jingyi; Manaenko, Anatol; Reis, Cesar; Chen, Sheng; Zhang, Jianmin (Experimental Neurology, 2024)
The authors regret that the picture in Fig. 6C was mistakenly picked in the article as originally published. The authors show the correct picture in the newly provided Fig. 6. This change will not have any effect on the results of the study.[Formula presented] The authors would like to apologise for any inconvenience caused.
CRIS-Team Scopus Importer:2024-05-03